Expanding genetic spectrum and discriminatory role of steroid profiling by LC‐MS/MS in 11β‐hydroxylase deficiency. (4th December 2020) - Karlekar, Manjiri Pramod; Sarathi, Vijaya; Lila, Anurag; Rai, Khushnandan; Arya, Sneha; Bhandare, Vishwambhar Vishnu; Atluri, Sridevi; Patil, Virendra; Ramteke‐Jadhav, Swati; Shah, Nalini S.; Kunwar, Ambarish; Bandgar, Tushar
Abstract: Objective: To report clinical, hormonal and structural effects of CYP11B1 pathogenic variations in Indian patients with 11β‐hydroxylase deficiency (11βOHD) and find hormonal criteria that accurately distinguish 11βOHD from 21α‐hydroxylase deficiency (21OHD). Design: Retrospective record review of genetically diagnosed patients with 11βOHD. Patients and Measurements: Clinical features, hormonal parameters at diagnosis (by immunoassay) and recent follow‐up of 13 genetically proven 11βOHD patients managed at our centre were retrospectively reviewed. ACTH‐stimulated serum adrenal steroids (measured by LC‐MS/MS) of 11βOHD were compared with those of simple virilizing and non‐classic 21OHD. Structural analysis of the observed pathogenic variations was performed by computational modelling. Results: Nine (four females) and four (all females) patients had classic and non‐classic disease, respectively. All 11βOHD patients had elevated ACTH‐stimulated serum 11‐deoxycortisol (26.5–342.7 nmol/L) whereas none had elevated serum 17‐hydroxyprogesterone (4.2–21.2 nmol/L); both hormonal parameters distinguished 11βOHD from 21OHD with 100% accuracy. ACTH‐stimulated serum cortisol, but not 11‐deoxycortisol, clearly distinguished classic (<70 nmol/L) from non‐classic (>160 nmol/L) disease. Thirteen (eight novel, two recurrent) pathogenic variants were observed. Only missense mutations were observed among patients with non‐classic disease. Computational modelling predicted the possible affection of enzyme structure and function for all the observed missense mutations. Conclusions: This first Indian study describes 13 11βOHD patients, including four with the rarer non‐classic variant. A total of eight novel pathogenic variants were identified in our study, highlighting regional genetic heterogeneity. Measurement of ACTH‐stimulated adrenal steroids by LC‐MS/MS will help avoid the misdiagnosis of 11βOHD as 21OHD and has potential to distinguish classic from non‐classic 11βOHD.